Comparison of the removal of phthalates and other organic pollutants from industrial wastewaters in membrane bioreactor and conventional activated sludge treatment plants - Llop, A (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
In recent years greater attention has been paid to the presence of pollutants in wastewater treatment plants, mainly because of strict environmental regulations and the possibility of reusing treated water in industrial processes. Since some organic pollutant compounds are not sufficiently removed in conventional activated sludge treatment (CAST) plants, new treatment processes have been developed, such as membrane bioreactors (MBRs). In this study a submerged membrane bioreactor (MBR) was used to treat mixed industrial wastewaters in parallel with a CAST plant. Two hydraulic retention times (HRT) of wastewater were tested as one of the operational conditions of MBR and the quality of effluents of the two processes were studied and compared. Several general quality parameters were analysed in wastewaters: chemical oxygen demand (COD), pH, conductivity, nitrogen, phosphate, suspended solids (SS) and turbidity. The two systems reduced COD by around 90%. SS was reduced by around 81% in the CAST plant and around 90% in the MBR plant. The results for the other general parameters were similar or better in the MBR process, which worked at a lower HRT. We also studied the removal of a group of six phthalates and bis(2-ethylhexyl)adipate ester by SPME/GC-MS in the two treatment plants. Most of these compounds were not completely removed in the two treatment plants and were identified at low microg l(-1) levels. We also tentatively identify some organic compounds in the wastewaters. Most of the compounds we found in the influent, MBR effluent and CAST effluent were benzene derivates, styrene, naphthalene and naphthalene derivates, and phenol derivates